Solitary wave solutions for a generalized KdV–mKdV equation with distributed delays - Du, Zengji; Wei, Dandan; Xu, Ying (Nonlinear Analysis: Modelling and Control, 2014)
This paper deals with a generalized KdV–mKdV equation with time delay. By employing the geometrical singular perturbation theory and the linear chain trick, we establish the existence result of solitary wave solutions when the average delay is sufficiently small, for a special convolution kernel.
Keywords: KdV–mKdV equation; solitary wave solutions; geometric singular perturbation; homoclinic orbit; time delay